Modulation of Immune Response and Tissue Repair Mechanisms in the Gill Filaments of Atlantic Salmon (Salmo Salar) Affected by Complex Gill Disease (Cgd) in a Marine Open Sea-Cage Environment - Vidal-Palomo, M; Vidal-Palomo, M; Goldstein-Vasquez, M; Reyes-Lopez, F; Vallejos-Vidal, E; Santillan-Araneda, M (Academic Press, 2025)
Complex gill disease (CGD) poses significant challenges in Atlantic salmon aquaculture, leading to reduced growth, higher production costs, and increased mortality rates. CGD is influenced by a multifactorial interaction of environmental factors and pathogens. Given the impact of CGD and the lack of molecular studies aimed at characterizing and modulating it, this study analyzed the modulation of genes and biological processes that occur in the CGD-affected gill filaments of Atlantic salmon. Gill samples were taken from CGD-affected fish at an open sea-cage marine farm in the Patagonian fjords of Chile (Aysen Region). Gills were portioned into damaged (CGDdt) and non-damaged (CGDndt) tissue for total RNA extraction and subsequent transcriptomic analysis by RNA-Seq, to identify differentially expressed genes and the biological functions to which they belong. As a control, gill filaments from healthy fish were also sampled. The CGDdt showed the upregulation of key genes such as mmp9, ccl19, and il8, indicating the promotion of a pro-inflammatory environment. In contrast, downregulation of processes associated with cellular homeostasis, cell communication, and structural development suggests altered tissue homeostasis and regeneration. By contrast, CGDndt registered an inhibition of the immune response and processes associated with tissue homeostasis maintenance, suggesting the promotion of mechanisms aimed at controlling the inflammatory environment and tissue damage due to the proximity with the branchial filament affected by CGD. In sum, this study provides valuable insights into the transcriptomic responses to CGD and the immune and tissue repair regulatory mechanisms in the mucosal tissues of aquatic organisms. © 2025 Elsevier Ltd